English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

....and also identifying a, b, and c.

2006-12-07 12:17:59 · 6 answers · asked by SICK MY DUCK! 1 in Science & Mathematics Mathematics

6 answers

y-6=3x(-6x+5)-2x^2+8

y-6 = -18x^2 + 15x - 2x^2 + 8-----I distributed the 3x

y-6 = -20x^2 + 15x + 8-------------I gathered like terms

y = -20x^2 + 15x + 14-----------I added 6 to both sides.

a= -20, b=15, c=14

2006-12-07 12:23:27 · answer #1 · answered by smaatgg 2 · 0 0

First multiply both binomials with techniques from utilising the tile, container or foil technique: f(x) = 2(3x^2 -x - 4) next, distribute both. f(x) = 6x^2 - 2x - 8 The values for a and b are... a = 6 and b = -2 (c = -8)

2016-11-30 07:12:29 · answer #2 · answered by Anonymous · 0 0

y = f(x) => y is a function of x in that it varies depending on the value of x.

f(x) = -20x^2+15x+14

a= -20, b= 15, c = 14

2006-12-07 13:53:42 · answer #3 · answered by bogey 4 · 0 0

work: y-6=3x(-6x+5)-2x^2+8
y-6=(-18x^2+15x)-2x^2+8
y-6= -20x^2+15x+8
y= =16x^2+15x+14
f(x)= -20x^2+15x+14
a= -20
b= 15
c=14

2006-12-07 12:30:49 · answer #4 · answered by monica 1 · 0 0

you are really stoopid for asking that. hahahahha. wow what math are you in, 6th grade algebra? bahahaha you are probably a high schooler to which is rather embarrassing.

2006-12-07 12:26:03 · answer #5 · answered by titsaremyforte 1 · 0 0

y-6=-18x^2+15x-2x^2+8
y-6=-20x^2+15x+8
y=-20x^2+15x+14
a=-20
b=15
c=14

2006-12-07 12:25:59 · answer #6 · answered by raj 7 · 0 0

fedest.com, questions and answers